2019
DOI: 10.1007/s40617-019-00355-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Stimulus Equivalence-Based Instruction to a Video Lecture to Increase Religious Literacy in Middle-School Children

Abstract: Being familiar with world religions and their diverse practices is referred to as religious literacy. The present study compared the effects of stimulus equivalence-based instruction (EBI) and video lecture (VL) to increase religious literacy in middle-school students; 10 participants were assigned to either the EBI or the VL group. Participants in the EBI group were taught five 6member equivalence classes using match-to-sample (MTS) software on a computer. Within each class of (1) Judaism, (2) Islam, (3) Chri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
4
2
Order By: Relevance
“…With regards to response generalization in the present study, increases in class-consistent responding observed during computerized tests for the participants in the EBI groups did not generalize to written test performances. This contrasts with the results of various prior EBI studies (e.g., Albright et al, 2016aAlbright et al, , 2016bFerman et al, 2020;Fields et al, 2009b). One possible explanation for this finding is that the written tests were inadequately sensitive to detect such changes.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…With regards to response generalization in the present study, increases in class-consistent responding observed during computerized tests for the participants in the EBI groups did not generalize to written test performances. This contrasts with the results of various prior EBI studies (e.g., Albright et al, 2016aAlbright et al, , 2016bFerman et al, 2020;Fields et al, 2009b). One possible explanation for this finding is that the written tests were inadequately sensitive to detect such changes.…”
Section: Discussioncontrasting
confidence: 90%
“…Although Brodsky and Fienup (2018) and Fienup and Critchfield (2011) noted there are advantages of EBI relative to traditional classroom or analog control condition teaching procedures (e.g., Critchfield, 2014;Ferman et al, 2020;Lovett et al, 2011;O'Neill et al, 2015), the results of the current study only moderately favor EBI over self-study. Despite the superiority of EBI during computer tests, there was a lack of differences among groups in written posttest performances.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The presentation order of the trial blocks for the baseline and derived relations followed a sequence known as a simple‐to‐complex protocol (Adams, Fields, & Verhave, 1993; Cowley et al, 1992; Ferman et al, 2020; Fields et al, 2009; Groskreutz, Karsina, Miguel, & Groskreutz, 2010). In this protocol, derived relations of increasing complexity are only tested after mastery has been demonstrated for prerequisite trained baseline relations (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…EBI has been used to teach a variety of skills with different populations of learners. These include world religions with middle school children (Ferman et al, 2020), geography to children diagnosed with autism (LeBlanc et al, 2003), coin values to children with autism (Keintz et al, 2011), fraction–decimal relations to typically developing students who demonstrated deficits (Lynch & Cuvo, 1995), music skills to a boy with autism (Arntzen, Halstadtro, Bjerke, & Halstadtro, 2010), and early braille literacy skills to children with visual impairments (Toussaint & Tiger, 2010), among others. With adults, these include studies in which EBI has been used to teach brain–behavior relations (Fienup et al, 2010), functions of behavior (Albright et al, 2016), statistics (Albright, Reeve, Reeve, & Kisamore, 2015; Fienup & Critchfield, 2010, 2011), and portion‐size estimation (Trucil, Vladescu, Reeve, DeBar, & Schnell, 2015), among others.…”
Section: Introductionmentioning
confidence: 99%